Epoxy Matrices Modified by Green Additives for Recyclable Materials. Issue 14 (22nd June 2017) - Henriksen, Martin L.; Ravnsbæk, Jens B.; Bjerring, Morten; Vosegaard, Thomas; Daasbjerg, Kim; Hinge, Mogens
Abstract: Epoxy‐based thermosets are one of the most popular matrix materials in many industries, and significant environmental benefits can be obtained by developing a recyclable variant of this widely utilized material. Incorporation of a bio‐based disulfide additive within a commercial epoxy system leads to a cross‐linked material that can be fractionated under mild and environmentally benign conditions. The material has been analyzed by FTIR and solid‐state NMR. Furthermore, modified epoxy matrices with low additive concentrations are demonstrated to have similar mechanical and thermal properties compared to commercially available benchmarks. Thus, additive formulation and fractionation based on green chemistry principles have been demonstrated, and a recyclable epoxy matrix has been developed. Abstract : Amicable breakup : Successful incorporation of the bio‐additivel ‐cystine into a commercial epoxy matrix shows very promising dismantling properties facilitated by acetic acid. This is accomplished without compromising thermal and mechanical properties of the materials compared to the unmodified epoxy matrix. The method enables a transition from the laboratory to sustainable industrial applications.